Front Cover: 3‐Acrylamidophenylboronic Acid‐Modified Hydrogel Film Attached to a Gold Nanosphere Array to Detect Hydrofluoric Acid with Good Selectivity and Recyclability (ChemNanoMat 2/2018). Issue 2 (16th January 2018) - Men, Dandan; Hang, Lifeng; Zhang, Honghua; Zhang, Xiaomin; Lyu, Xianjun; Cai, Weiping; Li, Yue
Abstract : A hydrofluoric acid (HF) sensor showed good recyclability and selectivity. The sensor was fabricated by embedding a 2D Au nanosphere array in a 3‐acrylamidophenylboronic‐acid‐functionalized hydrogel film. The hydrogel film swelled with increasing concentration of HF, resulting in a red shift of the diffraction wavelength. The concentration of HF could be detected by monitoring the wavelength of the diffraction spectra. More information can be found in the Communication by Yue Li et al. onpage 165 in Issue 2, 2018 (DOI:10.1002/cnma.201700228 ).